Application Of Demonstration Methods To Learning Arabic Language In MAS Taman Sidoarjo Islamic Boarding School - Habib Abdul Halim; Farid Qomaruddin; Muh Sabilar Rosyad (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
Demonstration is one method that can be used in Arabic learning, this method prioritizes visualization with the assumption that it can provide direct experience that students can directly see making it easier for students to understand teaching material. The purpose of this research is first to find out the relationship of the demonstration method to learning Arabic and the second is to find out whether there is an influence caused by the demonstration method on learning Arabic. This research method uses a quantitative approach with a pre-experimental design. The object of this research was the tenth grade students of Madrasah Aliyah at the MAS Islamic boarding school Taman Sidoarjo with a total of 21 students. Data collection techniques using documentation and tests with data analysis techniques using the SPSS 25 application through the Paired Sample T-Test formula. The results showed an increase in the average pre-test and post-test scores, from 61.43 to 78.57. There is a relationship between the pre-test and the post-test based on a significance value of .000 which is less than 0.05. There is an effect of the application of the demonstration method on learning Arabic with a Significance Level <0.05. From these results the researcher recommends that Arabic language educators be able to use demonstration methods in learning Arabic so that learning can be more effective. Because the demonstration method with its visualization properties is able to make students better understand the lesson visually so that concepts and skills can be formed more perfectly.